THE ANALYSIS OF THE APPLICATION OF ACCOUNTING INFORMATION SYSTEM MERCHANDISE INVENTORY AT PT. HASJRAT ABADI BRANCH TENDEAN - Palandeng, Olfiani E.; Karamoy, Herman (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
THE ANALYSIS OF THE APPLICATION OF ACCOUNTING INFORMATION SYSTEMÂ  MERCHANDISE INVENTORY AT PT. HASJRAT ABADI BRANCH TENDEAN